Epoxy/hollow glass microsphere syntactic foams for structural and functional application-A review. (15th May 2022) - Anirudh, S.; Jayalakshmi, C.G.; Anand, Anoop; Kandasubramanian, Balasubramanian; Ismail, Sikiru O.
Graphical abstract: Abstract: Composite materials have improved the fields of aerospace, marine and defence by supporting the manufacturing of several structures owing to their superior properties. The specific class of composite materials known as syntactic foams have come to the forefront for structural and functional applications. Therefore, the objective of this article was to present properties, material characterization, and applications of the new class of lightweight materials especially syntactic cellular foam made from the epoxy matrix and hollow glass microspheres (HGMs). The mechanical characterization of HGM filler–epoxy syntactic cellular foam for density, tensile properties, compressive properties, wear behaviour, fracture and impact toughness have been thoroughly reviewed along with dielectric properties. Finally, functional properties like buoyancy, acoustic, water-absorbing capability and the electromagnetic wave attenuation properties of epoxy/HGMs have been elucidated. Importantly, this succinct review stands to benefit both designers and developers/manufacturers of the aforementioned multi-functional materials for marine, electronics, aerospace and military/defence requisitions.